Enhancing the Cytotoxic Effects of Paclitaxel, Methotrexate, and Vincristine on Oral Cancer Cells with Curcumin - Ziaei, Seyed Mehdi; Khaje, Nasrin; Zaman, Mohammad; Ziaei, SeyedMehdi; Bagheri Shahzadeh Aliakbari, Razieh (Asian Pacific Journal of Cancer Biology, 2024)
Objective: Curcumin, a potent polyphenolic compound, has been closely studied for its potential to improve the efficacy of cancer treatments. With its antioxidant, anti-inflammatory, and anticancer properties, curcumin has shown promise in enhancing the cytotoxic effects of chemotherapeutic agents, especially in cancer cells that have developed resistance. Methods: This study investigated curcumin’s potential benefits in treating oral cancer. Researchers cultured CAL-27 oral cancer cells and treated them with varying concentrations of curcumin under standard laboratory conditions. To evaluate the effects on cell health and survival, they combined curcumin with common anticancer drugs such as paclitaxel, methotrexate, or vincristine. Results: The results were significant. Treating the CAL-27 cells with curcumin showed a noticeable decrease in cell viability, indicating that curcumin significantly inhibited cancer cell growth. This suggests that curcumin could potentially enhance the effectiveness of existing chemotherapy treatments for oral cancer. The study underscores the potential of curcumin as a complementary tool in the fight against oral cancer. Combining it with traditional chemotherapy could lead to better outcomes and improved management of this serious disease. Conclusion: These findings contribute to the growing body of research exploring natural compounds like curcumin as adjunct therapies in cancer treatment.